Kegiatan Festival Anak Sholeh di Yayasan Perguruan Ar Rahman - Arif Rahman; Fadia Ramadayanti; Halisa Saputri br. Bangun; Putri Rizky Ramadayanti; Rika Ayu Azhari (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2024)
This study aims to evaluate the implementation of Festival Anak Sholeh at Yayasan Perguruan Ar Rahman Misriadi, which focuses on increasing students' creativity and self-confidence in the religious field. The method used in this research is a qualitative approach with a descriptive design, which involves observation, interviews, and documentation. The research subjects consisted of religious teachers who acted as trainers and students from Madrasah Tsanawiyah (MTs) and Madrasah Ibtidaiyah (MI) levels. The results showed that the festival succeeded in increasing the spirit of learning religion, developing students' interests and talents in religion, and strengthening their self-confidence. Students were very enthusiastic in participating in various competitions, such as adhan and short verse recitation competitions, which were carried out in a structured manner with full support from the school. Nevertheless, this study also identified some constraints, such as limited space, lack of teacher participation in guiding students, and technical problems related to equipment. These constraints indicate the need for improvement in the implementation of the festival in the future so that it can be more optimal in achieving its goals. Thus, the Festival Anak Sholeh is not only a competition event, but also a means of strengthening character and Islamic values among students. This research provides recommendations for improvements in various aspects of the implementation of the festival so that it can be more effective in supporting the development of students' potential in the religious field.